Implantación de la contabilidad al “Consorcio Estadio”, ubicado en la ciudad de Cuenca, en el periodo de mayo hasta julio del 2014 - Malla Uyaguari, Ximena Del Rocío (2015)
The present thesis entitled IMPLEMENTATION OF ACCOUNTING TO "CONSORTIUM STADIUM", LOCATED IN THE CITY OF BASIN IN THE PERIOD FROM MAY TO JULY 2014, was developed to provide the Consortium under study a tool of basic accounting and generating useful information for better control of their business, the results will allow the attorney to make sound decisions for their optimal development. This research was developed as a prerequisite to obtaining Engineering Degree in Accounting and CPA Audit requirement. In developing this thesis was achieved meet the objectives, starting with obtaining the source, developing a plan and manual analysis, recording transactions in the Consortium documentation to the preparation of financial statements that provide data for a timely and reliable for making the right decisions. Upon completion of this research project was implemented in an accounting system Stadium Consortium during the period May to July 2014, allowing real results through the financial statements that will help your attorney to make decisions for their growth with order to achieve greater economic benefits.